2007
DOI: 10.1103/physrevlett.98.045502
|View full text |Cite
|
Sign up to set email alerts
|

Nondislocation Origin of GaAs Nanoindentation Pop-In Event

Abstract: The present Letter demonstrates a pop-in event that is caused by a nanoindentation-induced phase transformation in GaAs, and not accompanied by any dislocation nucleation. Our computer simulations reveal the appearance of the new phase, documented by the structural correlation functions and visualization of the atomic positions. This challenges the orthodox view that the initial pop-in event reflects nucleation of dislocations or their movement, and has a bearing on materials where dislocation activity is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 28 publications
2
43
0
3
Order By: Relevance
“…6(a) is in the range of 67.2-69.5 GPa and in good agreement with values reported in the literature. 21,22) At the indentation depth less than 200 nm, a ''staircase''-shaped P À h curve which is called displacement burst (or ''pop-in'') [23][24][25] is shown in Fig. 3(b).…”
Section: Mechanical Property and Representative Stressstrain Curvementioning
confidence: 99%
“…6(a) is in the range of 67.2-69.5 GPa and in good agreement with values reported in the literature. 21,22) At the indentation depth less than 200 nm, a ''staircase''-shaped P À h curve which is called displacement burst (or ''pop-in'') [23][24][25] is shown in Fig. 3(b).…”
Section: Mechanical Property and Representative Stressstrain Curvementioning
confidence: 99%
“…As a result, the relationship P= dE pot /dh [10] enabled us to determine the P-h curve with pop-ins initiated at indentation depths of h A 9 and h B 10 nm (Fig. 1).…”
mentioning
confidence: 99%
“…The study of nanoscale deformation when the surface of crystal is subjected to contact stress has proven that initial displacement transient events occurring in metals are the direct result of dislocation nucleation [2]. Our research revealed that this is not always true: instead of dislocation activity, nanoscale deformation may simply be due to phase transformation (semiconductor → metal), as predicted for GaAs by our earlier experiments and atomistic calculations [3]. Using a novel conductive nanoindentation technique, which is highly sensitive to structural changes under pressure [4], we discovered the essential link between this electrical phenomenon (current spike) and the mechanical transient (pop-in) exhibited by GaAs exclusively during nanoscale deformation.…”
Section: Introductionmentioning
confidence: 66%